2010
DOI: 10.11144/javeriana.upsy11-1.tpsb
|View full text |Cite
|
Sign up to set email alerts
|

Tipos de personalidad y síndrome de burnout en educadoras de párvulos en Chile

Abstract: El presente estudio tuvo por objetivo determinar niveles de Burnout en Educadoras de Párvulos en función de los tipos de personalidad y dependencias administrativas. Se diseñó un estudio no experimental, transversal descriptivo. Se evaluó el nivel de Burnout con la versión MBI para profesores y los estilos de personalidad con el instrumento NEO - FFI (n = 133). Se incluyó un cuestionario de variables sociodemográficas. Por medio de ANOVA ONEWAY se demostró que existen diferencias en el nivel de agotamiento emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Perceived stress showed statistically significant positive associations with burnout (P = 0.002, OR = 1.11, 95% CI: 1.04-1. 19).…”
Section: Correlates Of Burnout In Menmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived stress showed statistically significant positive associations with burnout (P = 0.002, OR = 1.11, 95% CI: 1.04-1. 19).…”
Section: Correlates Of Burnout In Menmentioning
confidence: 99%
“…Correlates of burnout among teachers include some organizational factors, such as adverse working conditions [6],work stress [12,13], lack of social support [14], interpersonal conflict [4], school type [15], administrative bureaucracy [5] and low salaries [5]. Meanwhile, several personal associations of burnout among teachers have also been indicated, such as age, education, marital status [16], emotional competence [17], temperament traits (emotional reactivity and perseveration), personality trait (extroversion, high neuroticism) [18,19], motives for selecting a teaching profession [20], approval of a position as teacher [21] and self efficacy [22].…”
Section: Introductionmentioning
confidence: 99%
“…Kindergarten education stands out for the multiplicity of its work, the duality of care/teaching, and the challenges they face daily. Here is recognized as an exhausting job, for example, with a high number of children per classroom (Ortiz Parada et al, 2012), in addition to being professionals subjected to high levels of stress, the product of a work overload and little time for distraction during their workday (Arteaga González et al, 2018). In this scenario where it is recognized to be a profession exposed to constant problems, the discussion is placed regarding how to identify the types of sources to which early childhood educators have access to favor the processes of searching for information that can help them to guide their educational processes or pedagogical decision making around these various problems experienced in their classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Correlates of burnout among teachers include some organizational factors, such as adverse working conditions [6],work stress [12,13], lack of social support [14], interpersonal conflict [4], school type [15], administrative bureaucracy [5] and low salaries [5]. Meanwhile, several personal associations of burnout among teachers have also been indicated, such as age, education, marital status [16], emotional competence [17], temperament traits (emotional reactivity and perseveration), personality trait (extroversion, high neuroticism) [18,19] In China, no known research has been conducted to investigate the prevalence and correlates of burnout in preschool teachers. Building on the available data, this present study was performed with the aim of exploring the level of self-reported burnout and some correlates of burnout among Chinese preschool teachers.…”
mentioning
confidence: 99%